Bringing together high school actors using mobile applications: a conceptual model proposal - Cunha, Carlos R. (2020)
Communication among the different actors present in the school ecosystem is an essential issue. However, in a hectic world where parents do not have much time to visit schools regularly, it is crucial to create mechanisms to better monitor student’s success and school demands. The interaction among school, students and parents presents a growing complex challenge. Technology has, in recent years, shaped the concepts of learning support and monitoring – both in school and out of school – as well as the way information flows among all actors in the school ecosystem. Emergently, the evolution of mobile applications, coupled with the evolution of mobile device capabilities, has made possible to create new and more effective intercommunication mechanisms, with ubiquitous approaches and in a predictable scenario of less willingness to physically interaction of the different actors. Based on these assumptions, this paper reflects on the potential of mobile devices and their applications to support new models of intercommunication among parents or school sponsors, students and teachers. Accordingly, a conceptual model is proposed that represents a work in progress that aims the creation and evaluation of a prototype system capable of improve de intercommunication and the overall success of the school learning system societal challenges.